Addressing the impact of rear surface passivation mechanisms on ultra-thin Cu(In, Ga)Se2 solar cell performances using SCAPS 1-D model. (15th November 2017) - Kotipalli, R.; Poncelet, O.; Li, G.; Zeng, Y.; Francis, L.A.; Vermang, B.; Flandre, D.
Highlights: We address the impact of rear surface passivation mechanisms on ultra-thin Cu(In, Ga)Se2 solar cell performances. The proposed model is validated for both field-effect and chemical passivation using a M-I-S test structure. We provide figures of merits without any significant loss in cell efficiencies for minimum net −Qf and maximum acceptable limit for Dit . We show the importance of rear reflectance on Jsc, while scaling down the CIGS absorber layers below 0.5 μm. We provide the optimal rear passivation layer parameters for efficiencies greater than 20% with ultra-thin CIGS thickness (<0.5 μm). We confirm that field-effect passivation with nano-point contact approach enhances the cell performances, especially for CIGS thickness below 0.6 μm. Abstract: We present a (1-D) SCAPS device model to address the following: (i) the surface passivation mechanisms (i.e. field-effect and chemical), (ii) their impact on the CIGS solar cell performance for varying CIGS absorber thickness, (iii) the importance of fixed charge type (+/−) and densities of fixed and interface trap charges, and (iv) the reasons for discrete gains in the experimental cell efficiencies (previously reported) for varying CIGS absorber thickness. First, to obtain a reliable device model, the proposed set of parameters is validated for both field-effect (due to fixed charges) and chemical passivation (due to interface traps) using a simple M-I-S test structure and experimentally extracted values (previously reported) into the SCAPS simulator. Next, we provide figures of merits without any significant loss in the solar cell performances for minimum net −Qf and maximum acceptable limit for Dit, found to be ∼5 × 10 12  cm −2 and ∼1 × 10 13  cm −2  eV −1 respectively. We next show that the influence of negative fixed charges in the rear passivation layer (i.e. field-effect passivation) is more predominant than that of the positive fixed charges (i.e. counter-field effect) especially while considering ultra-thin (<0.5 μm) absorber layers. Furthermore, we show the importance of rear reflectance on the short-circuit photocurrent densities while scaling down the CIGS absorber layers below 0.5 μm under interface chemical and field-effect passivation mechanisms. Finally, we provide the optimal rear passivation layer parameters for efficiencies greater than 20% with ultra-thin CIGS absorber thickness (<0.5 μm). Based on these simulation results, we confirm that a negatively charged rear surface passivation with nano-point contact approach is efficient for the enhancement of cell performances, especially while scaling down the absorber thickness below 0.5 μm.